A tapestry of secrets - Thomas, Sarah Loudin (Bethany House, a division of Baker Publishing Group, 2016)
Perla Phillips has carried a secret for over sixty years. When she sees her granddaughter, Ella, struggling in life, Perla decides to share her story--then suffers a debilitating stroke before she can do so. As Ella and her aunt begin to look into their grandmother's past, they'll learn more than they expected about Perla, faith, and each other.